Corticotropin-Releasing Factor receptor 1 (CRF1) antagonism in patients with alcohol use disorder and high anxiety levels: effect on neural response during Trier Social Stress Test video feedback - Lee, Mary R.; Rio, Daniel; Kwako, Laura; George, David T.; Heilig, Markus; Momenan, Reza (Neuropsychopharmacology (New York, N.Y.), 2023)
In preclinical models of alcohol use disorder, the corticotropin-releasing factor (CRF) receptor is upregulated, particularly in the extended amygdala. This upregulation is thought to play a role in stress-induced relapse to drinking by a mechanism that is independent of the hypothalamic-pituitary-adrenal axis. As part of a double-blind, placebo-controlled clinical study with pexacerfont, a selective, orally available, and brain-penetrant CRF1 receptor antagonist which has anti-anxiety effects in preclinical studies, we examined the effect of pexacerfont on the neural response to a social stress task adapted to fMRI. Subjects were 39 individuals (4 women) with high trait anxiety and moderate to severe alcohol use disorder randomized to receive pexacerfont or placebo. The task involved feedback of videoclips of an individual performing the Trier Social Stress Test. Pexacerfont had no effect on the neural response to self-observation under stress. The neural response to viewing oneself under stress vs an unknown other under stress activated prefrontal brain regions including insula, inferior frontal gyrus as well as medial, superior frontal gyri. These regions of activation overlap with those found in studies using similar paradigms. Potential applications of this task to probe neurocircuitry that is disrupted in addiction is discussed.